Pengaruh Pola Tidur Terhadap Pertumbuhan dan Perkembangan Anak Usia Dini - Syifa Amalya; Ismaniar Ismaniar; Lili Dasa Putri (STIKes Ibnu Sina Ajibarang, 2025)
Sleep patterns play a crucial role in supporting the growth and development of early childhood. Adequate and quality sleep contributes significantly to physical growth, cognitive development, emotional regulation, and social behavior in young children. However, changes in lifestyle, excessive screen exposure, and inconsistent daily routines often lead to irregular sleep patterns among early childhood learners. This study aims to analyse the influence of sleep patterns on the growth and development of early childhood. The research employs a literature review method by examining relevant journals, as well as authoritative books related to early childhood education and development. The findings indicate that children with regular sleep schedules and sufficient sleep duration demonstrate better physical growth, improved concentration, emotional stability, and optimal developmental milestones compared to children with irregular sleep patterns. In addition, parental involvement and educational environments, including nonformal education settings, play a significant role in shaping healthy sleep habits for children. These findings imply that collaboration between parents, educators, and nonformal education institutions is essential in fostering healthy sleep routines to support holistic child development. Therefore, awareness programs and educational interventions regarding sleep hygiene are necessary to optimize early childhood growth and development.